Ekstrakurikuler Tata Boga di SLB Negeri Keleyan Bangkalan - Irma Wahyu Ningrum; Nova Estu Harsiwi (Pusat Riset dan Inovasi Nasional, 2024)
Children with special needs are children who have special talents and interests and have different potential skills so they need to hone their potential skills. This research idn slot to describe and explain the results of the implementation of extracurricular culinary activities at SLB Negeri Keleyan, Bangkalan. A qualitative descriptive research methodology is used in this study. Three methods are used to acquire data: interviews, documentation, and observation. According to the research’s findings, extracurricular in a manner similar to that of curricular learning, which is founded on an independent curriculum. In this case, the raja slot demonstrates learning first before students practice directly. The results of this research show that: 1) learning planning for extracurricular culinary activities, 2) the implementation of extracurricular activities for culinary arts, 3) the link slot and infrastructure for extracurricular culinary arts, 4) supporting factors and inhibiting factors for the implementation of extracurricular culinary arts. The results of implementing these activities are that students are very enthusiastic about participating in these extracurricular activities.